CNE for NetWare 6 Study Guide - Clarke, David (Sams, 2004)
If you are studying for the Novell CNE certification tests 681, 682, 664 or 683, you need Novell's CNE Study Guide for NetWare 6 . It is the official Novell study guide and is the most effective tool to turn the passing rate in your favor. Loaded with illustrations, screen shots and hands-on exercises, it also includes sample test questions for all exams. A CD is included that provides you with a 3-user version of NetWare 6 server and NetWare 6 client software. Go after the most sought-after certification that Novell offers with this book in your hand.
Keywords: Local area networks (Computer networks) -- Study guides -- Management; Computer networks -- Study guides -- Management -- Examinations; Novell software -- Study guides -- Examinations; Réseaux locaux (Informatique); Gestion; Guides de l'étudiant; Réseaux d'ordinateurs; Gestion; Examens; Guides de l'étudiant; Logiciels Novell; Examens; Guides de l'étudiant; Computer networks; Management; Examinations; Local area networks (Computer networks); Management; Novell software; Examinations; Study guides